Assessment of Utilized Focused Educational Approaches Towards Enhancement of Community Knowledge, Attitudes, and Practices in Solid Waste Management - Rainiel Bryan V Domasian; Ofelia B Maningas; Jamine A Bautista; Jomar P Tañesa; Angelika Ross I Tagum; Francis A Martinez (Research Synergy Foundation, 2025)
This study examines the impact of the